Predictive Value of Serum Heat Shock Protein 90α on the Prognosis of Patients with Lung Adenocarcinoma - Fang Y; Yuan Z; Zhang H; Wang P; Hao J (Dove Medical Press, 2023)
Yue Fang,1,2 Zhichao Yuan,1 Hao Zhang,1 Peng Wang,3 Jiqing Hao1 1Department of Oncology, First Affiliated Hospital of Anhui Medical University, Hefei, People's Republic of China; 2Intern of Oncology, Hefei Cancer Hospital, Chinese Academy of Sciences (CAS), Hefei, People's Republic of China; 3Department of Anesthesiology, First Affiliated Hospital of Anhui Medical University, Hefei, People's Republic of ChinaCorrespondence: Jiqing Hao, Email haojiqing@ahmu.edu.cnPurpose: Heat shock protein 90α (HSP90α) is highly expressed in tumors, and predicts tumor progression. This study analyzed the correlation between the expression level of HSP90α in the serum and the prognosis of patients with lung adenocarcinoma.Patients and methods: The medical records of patients with 228 lung adenocarcinoma from September 2015 to December 2021 were analyzed. HSP90α expression in the patients' serum was detected by ELISA and the cut-off value (93.76 ng/mL) was determined according to the ROC curve, then the patients were divided into high- and low-level groups. The differences in the medical records of the two groups were compared using the X2 test, and Univariate and multivariate Cox regression analyses showed that serum HSP90α level were independent risk factors for both PFS and OS (P < 0.05).Results: HSP90α was positively correlated with TNM staging (P < 0.01) by One-way analysis of variance. The results of the correlation analysis and the Kaplan-Meier survival curve showed that the expression levels of HSP90α and CEA of patients were positively correlated (R=0.54, P < 0.001), and patients with high HSP90α and CEA levels had the worst OS (P < 0.001).Conclusion: HSP90α expression is negatively correlated with the prognosis of patients with lung adenocarcinoma and is a potential prognostic marker.Keywords: heat shock protein 90α, lung adenocarcinoma, prognosis, CEA